Non-magnetic member and method of manufacturing same
Patent Information
- Application Number
- JP2021189787
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-11
- Filing Date
- 2021-11-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-11-24
AI Technical Summary
【0012】 (2)本発明の非磁性部材(電磁用部材)は、高比抵抗と高強度を発現するチタン合金を備える。このため、高周波数(例えば高回転数)域の交番磁界中で使用されるときでも、非磁性部材に発生する渦電流損の低減が図られる。また、高速運動(回転、往復動等)により大きな力(遠心力、慣性力等)が作用し得るときでも、非磁性部材の薄肉化、軽量化、小型化等が可能となる。
Smart Images

Figure 0007635112000002 
Figure 0007635112000003 
Figure 0007635112000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-magnetic member or the like used in an alternating magnetic field. [Background technology]
[0002] There are various types of equipment that utilize electromagnetism (simply referred to as "electromagnetic equipment"), such as electric motors (including generators as well as motors) and actuators, and many of these equipment utilize alternating magnetic fields. In order to save energy, it is necessary to reduce high-frequency losses in such electromagnetic equipment when they are used in an alternating magnetic field. In particular, in electric motors that rotate at (ultra-) high speeds, there is a strong need to reduce eddy current losses, which increase in proportion to the square of the rotation speed (frequency of the alternating magnetic field). For example, the rotor cores and stator cores of motors are often constructed by laminating electromagnetic steel sheets covered with an insulating layer to suppress eddy currents that occur in a direction perpendicular to the alternating magnetic field.
[0003] However, for some components (called "electromagnetic components") used in alternating magnetic fields, it is difficult to adopt such a configuration. In such cases, it is necessary to reduce eddy current loss by constructing the electromagnetic components from a material with high electrical resistivity (simply called "resistivity").
[0004] The electromagnetic components disposed in the magnetic circuit are not limited to magnetic materials, and may be non-magnetic materials. Furthermore, the electromagnetic components may be required to satisfy not only electrical characteristics (e.g., resistivity) and magnetic characteristics (e.g., magnetic permeability), but also certain mechanical characteristics (rigidity, strength, ductility, etc.). The following patent documents contain descriptions related to such electromagnetic components: [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2001-339886 [Patent Document 2] Patent Publication No. 2008-29153 [Patent Document 3] Japanese Patent Application Laid-Open No. 2020-43746 [Patent Document 4] Japanese Patent Application Laid-Open No. 5-5142 [Patent Document 5] Japanese Patent No. 3712614 (WO2000 / 005425) [Patent Document 6] Japanese Patent Application Laid-Open No. 2005-320618 [Patent Document 7] Japanese Patent Application Laid-Open No. 2005-524774 (WO2003 / 095690) [Patent Document 8] U.S. Patent No. 4731115 [Summary of the Invention] [Problems to be Solved by the Invention]
[0006] Patent Documents 1 and 2 describe, as an example of an electromagnetic member made of a non-magnetic material (referred to as a "non-magnetic member"), a protective tube (sleeve) made of carbon fiber reinforced plastic (CFRP). The protective tube is fitted on the outer peripheral side of a cylindrical permanent magnet provided on the outer peripheral side of the rotor shaft (rotating shaft) of a motor. The protective tube prevents damage to the permanent magnet on which a large centrifugal force acts during high-speed rotation. However, when the rotational speed is further increased, the mechanical properties of the protective tube made of CFRP are not always sufficient.
[0007] Patent Document 3 proposes a non-magnetic member made of a titanium-based composite material. The titanium-based composite material is formed by dispersing reinforcing particles made of TiCy (0 < y < 1) with a partial deficiency of C in a matrix made of Ti-6%Al-4%V or the like. This non-magnetic member has a high specific resistance, high strength, and high rigidity.
[0008] Incidentally, Patent Documents 4 to 8 also describe titanium alloys or titanium-based composite materials, but there is no specific description regarding electromagnetic members or their specific resistance.
[0009] The present invention has been made in view of such circumstances, and an object thereof is to provide a non-magnetic member using a titanium alloy different from the conventional ones. [Means for solving the problem]
[0010] As a result of intensive research by the inventors to solve this problem, they succeeded in obtaining a titanium alloy having a composition different from that of the conventional one and exhibiting high resistivity and high strength. By expanding on this result, they have completed the present invention described below.
[0011] <Non-magnetic member> (1) The present invention is a non-magnetic member used in an alternating magnetic field, comprising a titanium alloy containing, by mass relative to the entire alloy, an α-phase stabilizing element having an Al equivalent of 5.5 to 11, and a β-phase stabilizing element having a Mo equivalent of 6 to 17, wherein the β-phase stabilizing element contains Fe and Mn.
[0012] (2) The non-magnetic member (electromagnetic member) of the present invention comprises a titanium alloy that exhibits high resistivity and high strength. Therefore, even when used in an alternating magnetic field in the high frequency range (e.g., high rotation speed), the eddy current loss generated in the non-magnetic member is reduced. In addition, even when a large force (centrifugal force, inertial force, etc.) may act due to high speed motion (rotation, reciprocation, etc.), the non-magnetic member can be made thinner, lighter, and smaller.
[0013] The reason why the titanium alloy according to the present invention exhibits high resistivity and high strength is not necessarily clear. At present, it is believed that the α-phase stabilizing element with a high Al equivalent and the β-phase stabilizing element with a high Mo equivalent act synergistically to obtain a titanium alloy that achieves both resistivity and strength at a high level. In particular, it is believed that the magnetic element Fe is dissolved in Ti to improve the resistivity of the non-magnetic titanium alloy. Also, it is believed that the strength of the titanium alloy is significantly improved by the inclusion of Mn, provided that the Al equivalent and Mo equivalent are within a predetermined range.
[0014] 《Manufacturing method》 The present invention can also be understood as a method for manufacturing the above-mentioned non-magnetic member and titanium alloy. For example, when the titanium alloy is made of a sintered material, the non-magnetic member is obtained by a sintering process for obtaining a sintered body from powder and a processing process for forming the sintered body into a desired shape according to the non-magnetic member. Furthermore, the titanium alloy made of the sintered material can exhibit excellent high resistivity and high strength even if it is not necessarily subjected to a special heat treatment (e.g., solution treatment or aging treatment) after the processing process. Of course, the titanium alloy according to the present invention is not limited to a sintered material, and may be a melt-cast material.
[0015] "others" (1) In this specification, the α-phase stabilizing element is an alloying element that increases the allotropic transformation temperature (about 885°C) of pure titanium and expands the α-phase region. The β-phase stabilizing element is an alloying element that decreases the allotropic transformation temperature and expands the β-phase region. In other words, the α-phase stabilizing element is an element that appears in the formula for calculating the Al equivalent, and the β-phase stabilizing element is an element that appears in the formula for calculating the Mo equivalent. In this specification, even alloying elements (Sn, Zr, etc.) that are generally considered to be neutral elements (completely soluble elements) are treated as α-phase stabilizing elements or β-phase stabilizing elements as long as they are alloying elements that affect the allotropic transformation temperature or equivalent. Of course, the titanium alloy according to the present invention may further contain a neutral element (alloying element that does not affect the allotropic transformation temperature) that does not affect the allotropic transformation temperature or equivalent.
[0016] The degree of "non-magnetic" (magnetic permeability) referred to in this specification may be within a range that does not short-circuit the magnetic circuit of an electromagnetic device. In this specification, electromagnetic components that contain a non-magnetic titanium alloy and are used in an alternating magnetic field are referred to as non-magnetic components. The non-magnetic component does not have to be entirely made of a titanium alloy, and the entire component does not necessarily have to be non-magnetic. In short, it is sufficient that at least a portion of the non-magnetic component of the present invention is made of a titanium alloy.
[0017] (2) Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit value or upper limit value to create a new range such as "a to b". Furthermore, "x to y μΩm" in this specification means x μΩm to y μΩm. The same applies to other unit systems (MPa, GPa, etc.). [Brief description of the drawings]
[0018] [Figure 1A] 1 is a structural photograph (SEM image) of the titanium alloy of sample 2. [Figure 1B] This is an enlarged photograph (SEM image) of the structure. [Diagram 2] 1 is a structural photograph (SEM image) of the titanium alloy of sample 3. [Diagram 3] FIG. 2 is an explanatory diagram showing a method for measuring resistivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] One or more components selected arbitrarily from this specification may be added to the components of the present invention described above. The contents described in this specification apply not only to the non-magnetic member but also to the manufacturing method thereof. The components may be method-related or product-related. Which embodiment is best depends on the target, required performance, etc.
[0020] Titanium alloy (1) Composition The titanium alloy preferably contains an α-phase stabilizing element with an Al equivalent of 5.5 to 11, 6 to 10, 7 to 9.5, or even 8 to 9 (or less), and a β-phase stabilizing element with a Mo equivalent of 6 to 17, 6.5 to 15, 7 to 12, or even 8 to 11.5. If the Al equivalent is too small, the resistivity becomes insufficient, and if it is too large, the elongation becomes small. If the Mo equivalent is too small, the strength becomes insufficient, and if it is too large, the elongation becomes small.
[0021] Here, the Al equivalent ([Al” eq) and Mo equivalent ([Mo” eq) are calculated as follows (Source: Light Metals, Vol. 55, No. 2 (2005), pp. 97-102). [Al” eq=[Al]+[Zr] / 6+[Sn] / 3+10[O]+16.4[N]+11.7[C] [Mo” eq=[Mo]+[Ta] / 5+[Nb] / 3.5+[W] / 2.5+[V] / 1.5+1.25[Cr] +1.25[Ni]+1.7[Mn]+1.7[Co]+2.5[Fe] However, in the present invention, unless otherwise specified, the Al equivalent is defined based on Al, Zr, and Sn, which are the main α-phase stabilizing elements ([Al] eq = [Al] + [Zr] / 6 + [Sn] / 3).
[0022] In this specification, the composition ratio (concentration) is a mass ratio (mass%) and is simply indicated by "%" unless otherwise specified. In the above calculation formula, [ ] indicates the mass ratio (%) of each alloy element to the entire titanium alloy. In the case of a titanium-based composite material in which reinforcing particles (e.g., TiC, TiB, etc.) are contained in the titanium alloy (matrix), the Al equivalent and Mo equivalent are calculated as the mass ratio to the entire matrix.
[0023] The α-phase stabilizing element may be, for example, Zr, Sn (neutral element), etc., in addition to Al. A representative element, Al, may be contained in an amount of, for example, 7 to 10% or even 8 to 9% relative to the entire titanium alloy (100 mass%).
[0024] Examples of the β-phase stabilizing element include Mo, V, Mn, Fe, etc. Representative elements include Mo, for example, 1 to 5%, or even 1.5 to 4%, and V, for example, 4 to 8%, or even 5 to 7% relative to the entire titanium alloy.
[0025] Furthermore, the titanium alloy may contain 0.5 to 3.5%, 0.9 to 3%, or even 1 to 2.5% of Fe, which contributes to improving resistivity, and 0.2 to 3%, 0.4 to 2.5%, or even 0.5 to 1.5% of Mn, which contributes to improving strength.
[0026] Furthermore, the titanium alloy may contain 0.1 to 1%, 0.2 to 0.7%, or even 0.3 to 0.5% of S, which contributes to improving machinability, etc. Although S is not essential, the inclusion of S is expected to improve machinability. However, excessive S may embrittle the titanium alloy.
[0027] Titanium alloys contain impurities (such as O and N) that are technically and economically difficult to remove or unavoidable. For example, O may be contained in an amount of about 0.1 to 0.7%, or even about 0.2 to 0.5%, based on the entire titanium alloy.
[0028] (2) Organization The metal structure of a titanium alloy (simply referred to as "structure") can change depending on the manufacturing process and heat treatment. The structure differs, for example, depending on whether the material is ingot or sintered, and even in the case of sintered material, it also differs depending on whether heat treatment is performed or not and the heat treatment conditions. However, since the titanium alloy according to the present invention has a sufficiently large Al equivalent and Mo equivalent, it is likely to have a metal structure in which α phase and β phase are mixed, regardless of the specific form.
[0029] As an example, in a titanium alloy made of a sintered material, a composite structure is obtained in which a hexagonal close-packed lattice structure (referred to as an "hcp structure") is distributed in an island-like manner in a body-centered cubic lattice structure (referred to as a "bcc structure") (see FIG. 1A). The bcc structure is mainly composed of β phase, and the hcp structure is mainly composed of α phase. More specifically, the bcc structure is mainly composed of the base element Ti and one or more β-phase stabilizing elements (Mo, Fe, V, etc.). The hcp structure is mainly composed of the base element Ti and one or more α-phase stabilizing elements (Al, etc.). The bcc structure may contain one or more α-phase stabilizing elements. Similarly, the hcp structure may contain one or more β-phase stabilizing elements.
[0030] The hcp structure occupies, for example, 30 to 70 volume %, 37 to 67 volume %, or even 43 to 60 volume % of the entire composite structure. Incidentally, the hcp structure is, for example, an aggregate of needle-like or granular ultrafine structures. For example, each ultrafine structure has a maximum length of 2 μm or less, or even 1 μm or less, and an aspect ratio (maximum length / minimum length) of 3 to 20, or even 5 to 10. The volume fraction, size, and aspect ratio of each structure (phase) are determined by analyzing (calculating) two-dimensional optical microscope photographs (images) using analysis software: ImageJ (open source program).
[0031] The above-mentioned composite structure is a structure not seen in conventional titanium alloys, but the correlation between the structure of titanium alloys and their properties (resistivity, strength, etc.) is not clear at present.
[0032] (3)Characteristics Titanium alloys exhibit excellent electrical and mechanical properties. For example, they exhibit resistivity of 2 to 5 μΩm, 2.1 μΩm to 4 μΩm, or even 2.2 μΩm to 3 μΩm. Such resistivity is far greater than that of pure Ti (about 0.4 μΩm) or that of a typical titanium alloy (Ti-6%Al-4%V) (about 1.7 μΩm). In this specification, the resistivity is determined by measuring a sample (bulk material) of a given size using a DC four-terminal method (see FIG. 3), unless otherwise specified.
[0033] The titanium alloy can exhibit high strength, for example, a tensile strength (fracture strength) of 1200 to 1700 MPa, 1250 to 1650 MPa, or even 1350 to 1550 MPa, a 0.2% proof stress of 1150 to 1600 MPa, or even 1200 to 1500 MPa, and a Young's modulus of 115 to 135 GPa, or even 120 to 130 GPa.
[0034] Furthermore, titanium alloys have an elongation of, for example, about 0.2 to 2%, or even about 0.4 to 1.5%, and can be plastically worked into non-magnetic members.
[0035] 《Manufacturing method》 The titanium alloy (non-magnetic member) can be manufactured by, for example, a sintering method, a melting method, a (powder) additive manufacturing method (so-called 3D printer), etc. As an example, the case of manufacturing a titanium alloy by a sintering method will be described below.
[0036] The sintering method is a method in which a powder compact is heated to obtain a sintered body. If the compact or sintered body is close to the shape of a non-magnetic member (i.e., if it is near-net shape), post-processing can be reduced. Of course, the sintered body may be subjected to plastic processing such as forging or pressing in a cold or hot state.
[0037] (1) Powder Usually, a mixed powder obtained by blending (weighing) a plurality of kinds of raw material powders is used for molding and sintering. In addition to simple substance powders, alloy powders, compound powders, etc. are used as raw material powders. For example, Ti source powder (pure Ti powder) is an example of simple substance powder. For example, Al-V powder, Ti-Al powder, Fe-Mo powder (ferromolybdenum powder), etc. are used as alloy powders. For example, Mn-S powder (manganese sulfide powder), Fe-Mn powder (ferromanganese powder), etc. are used as compound powders. Note that even powders of the same type that have the same alloy elements have various composition ratios. An appropriate raw material powder may be selected according to the desired blend composition. In any case, by using alloy powders or compound powders rather than simple substance powders, it is possible to reduce raw material costs and to homogenize and stabilize the structure.
[0038] The average particle size (median diameter: D50) of each powder is, for example, 1 to 20 μm, or preferably 3 to 15 μm. The mixed powder is prepared using a V-type mixer, a ball mill, a vibration mill, or the like (mixing step).
[0039] (2) Molding process The mixed powder is molded, CIP (Cold Isostatic Pressing), RIP (Rubber Isostatic Pressing), or the like to form a molded body of a desired shape. The shape of the molded body may be close to the shape of the final member (non-magnetic member), or may be a billet (intermediate material shape) when processing is performed after the sintering process. The molding pressure can be appropriately adjusted, but is preferably, for example, 200 to 600 MPa, or further 300 to 400 MPa.
[0040] (3) Sintering process The compact is heated in a vacuum or in an inert gas to become a sintered body. The sintering temperature is, for example, 1150°C to 1400°C, or preferably 1200 to 1350°C. The sintering time is, for example, 3 to 25 hours, or preferably 10 to 20 hours. By using an appropriate sintering temperature and sintering time, a titanium alloy with high properties can be efficiently obtained. The above-mentioned molding process and sintering process may be performed simultaneously by HIP (Hot Isostatic Pressing) molding.
[0041] (4) Cooling process After the sintering step, the material may be cooled by furnace cooling or forced cooling (by introducing an inert gas, etc.) at a rate of, for example, 0.1 to 10° C. / s. By controlling the cooling rate, the structure and properties of the titanium alloy may be adjusted.
[0042] (5) Processing process The sintered body may be used as a non-magnetic member as it is, or may be processed into a non-magnetic member by plastic working, cutting, or the like. The plastic working may be cold working or hot working. Hot working can suppress cracks and the like and produce a non-magnetic member with a good yield. Cooling after hot working may be furnace cooling, but air cooling is also sufficient.
[0043] The titanium alloy according to the present invention can exhibit the desired structure and characteristics without the need for heat treatment such as solution treatment, aging treatment, etc. Such a non-heat-treatable titanium alloy contributes to reducing the manufacturing costs of non-magnetic members.
[0044] <Non-magnetic parts / electric devices> The non-magnetic member of the present invention has high resistivity, high strength, and low magnetic permeability, and is therefore suitable as an electromagnetic member used in an alternating magnetic field. Although the specific use is not important, it can be used, for example, as a protective member (protective tube, protective case) for a permanent magnet (field source) incorporated in an electric motor (electromagnetic device, electric device) (see JP 2020-43746 A mentioned above). An example of such an electric motor is a centrifugal compressor that requires high rotation. Such a compressor is used, for example, in an engine supercharger or an air compressor for a fuel cell. EXAMPLES
[0045] Various samples (sintered titanium alloys) with different component compositions were produced, and their electrical properties (resistivity) and mechanical properties (tensile strength, 0.2% yield strength, Young's modulus, elongation) were evaluated. The present invention will be described in more detail below with reference to these specific examples.
[0046] <Sample Preparation> (1) Raw material powder The Ti powder used was a commercially available hydrogenated and dehydrogenated powder (manufactured by Toho Tech Co., Ltd.) that had been classified using a sieve (#350, average particle size 75 μm).
[0047] As the alloy powder serving as the source of alloying elements, one or more of the following powders were used. (a) Al-40% V powder (average particle size: 9 μm / Kinsei Matec Co., Ltd.) (b) Ti-36%Al powder (average particle size: 9 μm / manufactured by Daido Steel Co., Ltd.) (c) Fe-60%Mo powder (average particle size: 45 μm / manufactured by Taiyo Koko Co., Ltd.) (d) MnS powder (average particle size: 9 μm / manufactured by Fukuda Metals Co., Ltd.) (e) Fe-78%Mn powder (average particle size: 10 μm / manufactured by Fukuda Metals Co., Ltd.)
[0048] Unless otherwise specified, the compositions shown in the present examples are the mass percentages (mass%) of each raw material powder or mixed powder relative to the total, and are simply indicated by "%". The average particle size of each powder was determined using a laser diffraction / scattering particle size distribution analyzer (MT3300EX / manufactured by Nikkiso Co., Ltd.). Each powder may contain a small amount of oxygen (impurity) that is inevitably adsorbed or bonded to the particle surface.
[0049] (2)Mixing process The raw powders were weighed and mixed to obtain the overall composition (Al equivalent, Mo equivalent) shown in Table 1 (except for samples C4 and C5). Each mixed powder was mixed in a V-type mixer for 1 hour to obtain a mixed powder for each sample.
[0050] (3) Molding process Each mixed powder was placed in a polyvinyl chloride tube (PVC) and CIP molded to obtain a round rod-shaped molded body (approximately φ16mm × 150mm). The molding pressure at this time was 4t / cm 2 (392 MPa).
[0051] (4) Sintering process Each compact was placed in a vacuum (1×10 -5 The sample was sintered by heating at 1300°C for 16 hours at a pressure of 1200 torr. The heating rate up to the sintering temperature was about 5°C / min, and the cooling rate after the sintering time had elapsed was 10°C / s.
[0052] (5) Processing process Furthermore, the sintered bodies of each sample were hot worked (forged) in an air atmosphere. The heating temperature was 1200°C, and the working ratio was 56%. The working ratio here was calculated as the reduction in area (Aw / Ao). Aw is the cross-sectional area after working, and Ao is the cross-sectional area before working.
[0053] The sintered body (worked product) after hot working was cooled in air to lower the temperature, and no heat treatment was performed after air cooling. Various measurements and observations were performed using each test material (billet) obtained in this way.
[0054] (6) Casting material (comparison example) For samples C4 and C5 shown in Table 1, commercially available ingot materials (manufactured by Daido Steel Co., Ltd.) were used as they were.
[0055] "measurement" (1) Electrical properties (resistivity) The resistivity of each sample was determined as shown in FIG. 3. Specifically, first, electrodes were formed on a prism (3.014 mm (t) × 3.014 mm (w) × 20 mm) made from each test material as follows. The center part of each prism (voltage electrode interval (L): 10 mm) was masked with masking tape. Terminal wires (silver wire: φ0.20 mm) were wound around the masked end parts and the two outer parts, which are four places (see FIG. 3). Silver paste (Dotite D-550, manufactured by Fujikura Kasei Co., Ltd.) was applied to the parts where the terminal wires were wound and to both end faces of the prism. After application, the prism was heated in the air at 100°C for 12 hours to dry. In this way, a test piece equipped with a current electrode and a voltage electrode was prepared.
[0056] The resistivity (electrical resistivity) of each sample was calculated from the voltage (V) and current (I) values measured for each test piece by the DC four-terminal method at room temperature and the cross-sectional shape (S = t × w) of the test piece (rectangular column) (see formula (1) in Figure 3). The resistivity (measured value) of each sample thus obtained is also shown in Table 1.
[0057] (2) Mechanical properties (Young's modulus, tensile strength, elongation) A tensile test was carried out using a round bar tensile test piece (parallel part diameter: φ2.4 mm, gauge length: 14 mm) made from the test material, using an autograph (AUTOGRAPH AG-1 50 kN, manufactured by Shimadzu Corporation).
[0058] The tensile test was performed at room temperature in air at a strain rate of 5×10 -4The tensile test was carried out as a function of strain / s. Based on the stress-strain relationship calculated from the load-stroke diagram obtained from the load cell and video extensometer in this tensile test, the mechanical properties of each sample were determined (see JIS Z 2241:2011). The results are also shown in Table 1. The tensile strength was calculated based on the load at break and the initial shape of the test piece. The elongation is the strain of the test piece at break.
[0059] "observation" (1) The structure of the test materials before the tensile test was observed by a SEM (Scanning Electron Microscope). As an example, the observation images (SEM images) of sample 2 are shown in Figures 1A and 1B. Also, the SEM image of sample 3 is shown in Figure 2. Both Figures 1B and 2 show an enlarged island structure.
[0060] (2) The SEM images of the microstructures before the tensile tests were analyzed using ImageJ to determine the proportion of island structures in each sample. The results are also shown in Table 1.
[0061] (3) X-ray diffraction The structure before the tensile test was analyzed by X-ray diffraction (XRD / Cu-Kα). The results showed that the island structure was a hexagonal close-packed hcp structure, and the base structure surrounding it was a body-centered cubic bcc structure.
[0062] "evaluation" (1)Characteristics As is clear from Table 1, the titanium alloys of Samples 1 to 5, in which both the Al equivalent and the Mo equivalent were within the prescribed range and which also contained Fe and Mn, had high resistivity and high strength.
[0063] Moreover, titanium alloys that do not contain S, such as sample 5, have high resistivity, high strength, and high ductility even without heat treatment. Specifically, the titanium alloys exhibit tensile strength of 1600 MPa or more and elongation of 1% or more, achieving a high level of compatibility between strength and elongation, which are generally in a trade-off relationship.
[0064] On the other hand, specimens C1 and C2, which had a small Mo equivalent, had insufficient strength. Also, specimens C4 and C5, which had a small Al equivalent, had at least insufficient resistivity. Furthermore, specimen C3 had high resistivity because its Al equivalent and Mo equivalent were within the specified range, but because it did not contain Mn, its strength (especially 0.2% proof stress) was insufficient.
[0065] (2) Organization As is clear from Fig. 1A and Table 1, Samples 1 to 5 were found to have a composite structure in which many island-shaped hcp structures (simply referred to as "island structures") were surrounded by bcc structures. In addition, as can be seen from Fig. 1B and Fig. 2, it was found that the island structures were composed of an aggregate of needle-shaped or fibrous (ultra)fine structures. The SEM images also revealed that each fine structure had a maximum length of 2 μm or less and an aspect ratio of 5 or more.
[0066] It was confirmed by actual machining that all of the titanium alloys of samples 1 to 4 had better machinability than the titanium alloys of samples C1 to C5.
[0067] From the above, it was found that titanium alloys containing Fe and Mn, with both Al equivalent and Mo equivalent within the specified range, have high resistivity and high strength, and are suitable for nonmagnetic electromagnetic components (nonmagnetic components). It was also found that such titanium alloys have a unique structure in which a hcp structure (island structure) consisting of a collection of fine structures is dispersed in a bcc structure.
[0068] [Table 1]
Claims
1. A non-magnetic member used in an alternating magnetic field, A non-magnetic member comprising a titanium alloy containing an α-phase stabilizing element having an Al equivalent of 7 to 11 and a β-phase stabilizing element having a Mo equivalent of 6 to 17, the composition ratio being as follows, in terms of mass ratio relative to the entire alloy: Al: 7 to 10%, Mo: 1 to 5%, Fe: 0.5-3.5%, Mn: 0.2-3%, The balance is Ti and impurities.
2. 2. The non-magnetic member according to claim 1, wherein the titanium alloy further contains 4 to 8% V by mass relative to the total mass of the titanium alloy.
3. 3. The non-magnetic member according to claim 1, wherein the titanium alloy further contains S at a mass ratio of 0.1 to 1% relative to the total mass of the titanium alloy.
4. The non-magnetic member according to any one of claims 1 to 3, wherein the titanium alloy is composed of a composite structure in which a hexagonal close-packed lattice structure (referred to as "hcp structure") is distributed in an island shape in a body-centered cubic lattice structure (referred to as "bcc structure").
5. 5. The non-magnetic member according to claim 4, wherein the hcp structure accounts for 30 to 70 volume % of the entire composite structure.
6. 6. The non-magnetic member according to claim 1, wherein the titanium alloy has a resistivity of 2 μΩm or more.
7. 7. The non-magnetic member according to claim 1, wherein the titanium alloy has a 0.2% yield strength of 1150 MPa or more.
8. 8. The non-magnetic member according to claim 1, wherein the titanium alloy is made of a sintered material.
9. 9. A method for producing a non-magnetic member according to claim 8, comprising the steps of: a sintering step for obtaining a sintered body from the powder; and a processing step of forming the sintered body into a desired shape corresponding to the non-magnetic member. The method for producing a non-magnetic member includes obtaining the titanium alloy without at least performing a solution treatment after the processing step.
10. 10. The method for producing a non-magnetic member according to claim 9, wherein the powder contains at least a ferromolybdenum powder and a manganese sulfide powder.
Citation Information
Patent Citations
Titanium-based composite material and production thereof
JP1993005142A
High touchness titanium alloy and production thereof
JP1993009629A
Rotor and manufacturing method thereof, and rotating machine
JP2001339886A
HIGH-STRENGTH alpha-beta TITANIUM ALLOY
JP2005076098A
High-strength alpha+beta-type titanium alloy
JP2005320618A